Rationales of delay and difference in regulatory review by Japan, the USA and Europe among new drugs first approved in Japan. Issue 8 (5th March 2021) - Tanaka, Mototsugu; Idei, Mayumi; Sakaguchi, Hiroshi; Kato, Ryosuke; Sato, Daisuke; Sawanobori, Kenji; Kawarasaki, Shuichi; Hata, Toshiyuki; Yoshizaki, Asako; Nakamura, Miki; Ikuma, Mutsuhiro
Abstract : Aims: To clarify the rationales of delay or difference in the review of new drug applications among regulatory authorities for new drugs, those first approved in the world being in Japan. Methods: Among 80 new drugs first approved in Japan from 2008 to 2019, we identified those subsequently approved in the USA or Europe. Significant delays in approval time (boxplot outliers ) and the rationales for the delays were assessed among the Pharmaceuticals and Medical Devices Agency (PMDA), the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Results: Of the 80 Japan‐first approvals, 25 and 24 were approved in the USA and Europe, respectively, and their median approval times in Japan, the USA and Europe were 285, 334 and 477 days, respectively. Significant delays were identified for pirfenidone (1806 days, FDA), alogliptin benzoate (1856 days, FDA), insulin degludec (1457 days, FDA) and romosozumab (750 days, PMDA; 994 days, FDA; 748 days, EMA). Due to concerns about cardiovascular risk, alogliptin benzoate and insulin degludec were requested for additional clinical trials by the FDA, and romosozumab required a much longer review period than the standard approval time in all three regions. Conclusions: Among the new drugs significantly delayed in approval time in Japan, the USA or Europe, there were some differences in the requirements, the participating regions and the assessment of clinical trials. The regulatory views on the cardiovascular risk also differed among the three regions. These divergences may be associated with the differences in approval histories. Abstract :